TATA KELOLA SISTEM INFORMASI PADA MEDIA INTERNAL AMS (APLIKASI MANAJEMEN SURAT) SEBAGAI SARANAPENYAMPAIAN INFORMASI DI PT. PLN (PERSERO) WILAYAH RIAU DAN KEPULAUAN RIAU - Yunus, Finalia; Lubis, Evawani Elysa (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
PT. PLN (Persero) Region Riau and Riau Islands have Office Area 4, namely Dumai, Rengat, Cape nut and Pekanbaru. This makes pln must strive to meet every information needed throughout the PLN offices scattered in every part in Riau and Riau islands so that PLN using AMS as the internal media. Its presence helps in the process of delivering information PT. PLN (Persero) Region Riau and Riau Islands. So the purpose of this study was to determine how the planning, management, control, and assessment of internal media in disseminating information on PT.PLN (Persero) Region Riau and Riau Islands.This research receipts descriptive qualitative method. His research subjects are employees of PT. PLN (Persero) Region Riau and Riau Islands by using purposive sampling technique. The technique of collecting data through participant observation, interviews and documentation. For analyze the results of this study using analysis of technical data by Miles and Huberman through data reduction, while data validity checking techniques through extension of participation, and triangulation.Results of this study using the planning stages through the tiers of the formation of ideas and design by PT .PLN Center, execution, control, and evaluation carried out in the entire PT. PLN (Persero) spread throughout Indonesia in accordance with SOP (System Operational Procedure) as well as tailored to the needs of employees. Stage management is done according to SOP that has already been prepared. Phase control is done with training, assessment, and technical guidance that is done once a week according to the needs and the good cooperation between employees. Appraisal done on employees who actively access the internal media and obtained very satisfactory assessment and assist the employee in the process of delivering correspondence and data storage company.Keywords: governance, internal media, information delivery.